Accuracy of Radiographic Displacement Measurement in a Pelvic Ring Injury Model. Issue 2 (15th January 2022) - Hashmi, Sohaib Zafar; Butler, Bennet; Johnson, Daniel; Wun, Kelly; Sherman, Alan; Summers, Hobie; Stover, Michael
Abstract : Background: Pelvic ring injury outcome studies rely on radiographic assessment. To date, no study investigates the accuracy of radiographic measurement. The aim of this study was to assess the accuracy and interobserver reliability of pelvic ring displacement measurement in an injury model. We hypothesize that current radiographic measurement methods do not accurately quantify the three-dimensional pelvic ring displacement. Methods: Ten orthopaedic traumatologists evaluated 12 pelvic ring injury model displacements using AP, inlet, and outlet radiographs and axial CT images. Observers completed a survey of demographic and treatment approach strategies. Radiographic displacement measurements in axial, coronal, and sagittal planes were analyzed for accuracy using. Absolute displacement measurements were categorized with Matta and Tornetta grading system for Fleiss Kappa inter-reliability correlation evaluation. Results: The mean age of orthopaedic traumatologists was 47.5 years (range 36 to 59) with a mean 15.3 years (range 4 to 27) of pelvic fracture surgery experience. Radiographic measurement of isolated uniplanar of pelvic displacement in axial, sagittal, or coronal plane alone was more accurate than multiplanar pelvic displacements with more than one plane of displacement, 6.6 ± 5.7 mm error compared with 9.6 ± 6.3 mm error, respectively ( P = 0.0035). Measurement accuracy was greater with isolated coronal plane (4 ± 3.5 mm error) compared with isolated axial plane (9.9 ± 7.1 mm error) or isolated sagittal plane displacement (6.7 ± 4 mm error). Interrater reliability for the radiographic displacement measurement by observers showed an overall poor agreement with 0.24. Conclusion: Radiographic displacement measurement in these modeled pelvic ring injuries has notable inaccuracy among various measurement methods. Coronal and sagittal plane radiographic displacement measurements are more accurate compared with axial plane measurement. The reporting of radiographic displacement measurement outcomes in clinical research studies should be critically evaluated, and standardization of pelvic ring injury displacement may not be achievable with radiography. Level of Evidence: Level V